A step towards carbon neutrality in E7: The role of environmental taxes, structural change, and green energy. (1st July 2023) - Sarpong, Kwabena Agyarko; Xu, Wanzhen; Gyamfi, Bright Akwasi; Ofori, Elvis Kwame
Abstract: To achieve sustainable production and consumption patterns in the modern world, emerging countries are concentrating more on how economic variables may employ carbon neutrality targets appropriately. Using renewable energy, structural changes initiative, and imposing environmental taxes are all part of the plan to achieve the carbon neutrality goal in terms of reduced carbon emissions (CO2 ), haze pollutants, and greenhouse gases (GHG). Environmental taxation, renewable energy, structural changes, trade openness, and foreign direct investment (FDI) are aspects taken into account in this study, along with the long-term viability of the natural ecology in the E7 (China, Turkey, India, Russia, Brazil, Indonesia, and Mexico) economies. The Driscoll Kraay fixed effect OLS technique and the Method-of-Moment quantile (MMQ) regression technique were adopted for the baseline analysis for the data span of 2000 to 2020. From the empirical analysis, it was discovered that environmental Tax, structure change, and renewable energy have a negative connection with carbon emissions for the understudy countries. Moreover, the pollutant haven hypothesis (PHH) was confirmed since the findings discovered a positively significant relation involving FDI and carbon emission. Similarly, trade openness was seen to have a positive connection with carbon emissions. Thus, it is concluded that effective environmental taxation, renewable energy enhancement, and structure changes mitigate pollution while trade openness and FDI inflow enhance carbon emission for the E7 economies. According to the results, rigorous environmental tax rules will enable enterprises to transition manufacturing to green and sustainable alternatives. Finally, the report recommends that transferring tax money to research and development of sustainable technology programmes will enable governments to meet the SDG-7 and SDG-13 objectives of the United Nations. Highlight: Examine the effect of environmental Tax, renewable energy, and structural change on CO2 emission for E7 economies. Driscoll-Kraay and moment-of-moment quantile techniques are used in this study. Environmental tax, renewable energy and structure change improve the E7 economies' environment. The PHH as well as the trade-openness-CO2 nexus, are confirmed by the findings. Clean energy infrastructure and effective environmental Tax, as well as structural changes implementation, are essential for carbon neutralization for the E7 economies.